The image of the urban landscape and its photographic representation in the cities of Huancayo and Jauja from 1838 to 2018 - Martínez Vitor, César Fortunato (2019)
The objective of contrasting the image of the urban landscape and its photographic representation in the cities of Huancayo and Jauja from 1838 to 2018 was achieved, the applied research method was documentary and graphic with a comparative and retrospective design, it had two parts, the first qualitatively assessed the image of the urban landscape of the year 1838 confirming its attributes as an image and the narratives of the urban landscape of the cities under study. In the second, the photographic captures were made, for which the technical characteristics of the perspective of the image of the urban landscape of the year 1838, which guided the photographic captures in 2018, were structured. The technique of digital reconstruction of the image of the urban landscape of 1838 and its photographic representation of 2018, was achieved in several sequences of retrospective reconstruction settings. By fitting the photographic image of the urban landscape of 2018 on the image of the urban landscape of 1838, the final results were obtained, concluding that the image of the urban landscape of the year 1838 of the city of Huancayo has been modified and altered significantly and irreversibly, this condition does not occur with the city of Jauja that preserves in part the urban profile of the year 1838.